AFFECTIVE REACTIONS TO AI IN LISTENING LESSONS: STRESS, CONFIDENCE, AND ENJOYMENT (Modern education and development, 2025)
This article explores the affective (emotional) reactions that learners experience in AI-assisted listening lessons, particularly focusing on stress, confidence, and enjoyment. The study reveals that while artificial intelligence technologies provide pedagogical benefits such as real-time feedback and personalized learning, they may also increase psychological pressure, especially among students unfamiliar with digital platforms. At the same time, AI can foster self-confidence through adaptive tasks and nonjudgmental automated responses, allowing learners to improve at their own pace. Interactive and gamified AI tools contribute to making listening lessons more engaging and effective. In this way, AI influences learners not only cognitively but also emotionally—either positively or negatively—depending on its implementation. The article presents concrete examples of these reactions and offers recommendations for optimizing the use of AI in language learning to ensure both academic success and emotional well-being.